Mechanical properties of low-density heat-resistant polyimide-based advanced composite sandwich panels - AKIN, EMRE; ÇAKIR, MUSTAFA (WILEY, 2022)
This study presents low-density heat-resistant polyimide (PI)-based advanced composite sandwich panels (HRACS) consisting of carbon fiber-reinforced PI matrix thermoset and thermoplastic advanced composite laminates (outer faces) and PI foams (core materials). For the outer faces, thermoplastic composite laminates were prepared from poly (amic acid) ammonium salt precursor resin, and the thermoset was prepared from nadic anhydride (NA)-terminated poly (amic acid) precursor resin. 3,3,4,4-Benzophenone tetracarboxylicdianhydride and 4,4-diamino diphenylsulfone were used as monomers for the polymer backbones. For the thermosetting composite, NA was also used as an end capper and to provide crosslinking of the polymer chains. On the other hand, the HRACSs had two kinds of core materials with low densities. As core materials, isocyanate-based PI foams were used. Pyromellitic anhydride and polymeric diphenylmethane diisocyanate were used for the PI foams and the amounts of the additives such as the surfactant, water, and triethylamine. As a result of these variations, different compressive properties and densities were obtained. On the other hand, a polymerization of monomeric reactant (PMR)-type adhesive PI resin was synthesized in this study. The HRACSs were prepared with the curing and crosslinking of this synthesized PMR-type adhesive PI resin at the interfaces of the outer face and core materials. These HRACSs exhibited outstanding compressive and flexural properties. The flexural force of the HRACSs increased up to 535 N while the composite laminates exhibited values of 197 and 255 N. Additionally, the thermomechanical properties determined with dynamic mechanical analysis, especially those related to the composite faces, were promising.
Keywords: fiber-reinforced advanced composites; isocyanate-based polyimide foams; low-density heat-resistant sandwich composites; poly (amic acid) ammonium salt precursor resin; thermoplastic and thermoset composites; THERMOPLASTIC POLYIMIDE; CARBON; DIANHYDRIDE; FOAMS